2019
DOI: 10.1101/785626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DeepMicro: deep representation learning for disease prediction based on microbiome data

Abstract: AbstractHuman microbiota plays a key role in human health and growing evidence supports the potential use of microbiome as a predictor of various diseases. However, the high-dimensionality of microbiome data, often in the order of hundreds of thousands, yet low sample sizes, poses great challenge for machine learning-based prediction algorithms. This imbalance induces the data to be highly sparse, preventing from learning a better prediction model. Also, there has been little w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Dony et al [49] found that VAE with a VAMP prior is capable of learning biologically informative embeddings without compromising on generative properties. Oh et al [50] utilized various autoencoders to convert high-dimensional microbiome data into robust low-dimensional representations, and apply machine learning classification algorithms to the learned representations. Way et al [51] compared different methods include VAE to compress data dimensionalities and learn complementary biological representations.…”
Section: ) Sequence Structures Dimensionality Reduc-tionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dony et al [49] found that VAE with a VAMP prior is capable of learning biologically informative embeddings without compromising on generative properties. Oh et al [50] utilized various autoencoders to convert high-dimensional microbiome data into robust low-dimensional representations, and apply machine learning classification algorithms to the learned representations. Way et al [51] compared different methods include VAE to compress data dimensionalities and learn complementary biological representations.…”
Section: ) Sequence Structures Dimensionality Reduc-tionmentioning
confidence: 99%
“…In addition, a key benefit of VAEs is the ability to control the distribution of the latent representation vector z, which can combine VAEs with representation learning to further improve the downstream tasks [18,22]. Moreover, the generated image quality and diversity are improved by the existing VAE-variants such as β-VAE [23] and InfoVAE [24], which combine VAEs with disentanglement [25], [26], [27], [28], [29], [30], [31] graph representation design [32], [33], [34], [35], [36], [37], [38], [39], [40] sequence datasets analyses sequence engineering [41], [42], [43], [44], [45], [46], [47] dimensionality reduction [48], [49], [50], [51], [52], [53], [54], [55] integrated multi-omics data analyses [56], [57] predict effects of mutations [58], [47] gene expression analyses [56], [59], [54], [60], [61], [57]<...>…”
Section: Introductionmentioning
confidence: 99%
“…relative abundances. This approach is commonly used in DL (Oh and Zhang, 2020), although it brings with several disadvantages, in that it does not remove compositionality (Aitchison, 1982). As such, several standard analyses cannot be applied without bias, such as comparative analysis between groups; however, these problems are distinct from how we use this approach in our study.…”
Section: Normalizationmentioning
confidence: 99%
“…The study most similar to ours is DeepMicro (Oh and Zhang, 2020). Here, we predict a microbiome code from environmental variables and then decode it to obtain the whole microbiome vector using an Au-toencoder.…”
Section: Comparison With Similar Approachesmentioning
confidence: 99%
See 1 more Smart Citation